Respuesta :

Kesja

Answer:

Please see below.

Step-by-step explanation:

f^-1 (x) essentially means the reverse.

We can substitute y for x in the equation and solve for y:

x = 4y -1

x+1 = 4y

y = (x+1)/4

so that is our answer for the first one:

f^-1(x) = (x+1)/4

We do the same trick for the second question:

x = 2y +1

x-1 = 2y

y = (x-1)/2

so the answer is f^-1(x) = (x+1)/2

The last question is slightly more complex, we can write is as:

x = 2y/(y-1)

x(y-1) = 2y

yx -x = 2y

yx = 2y + x

yx - 2y = x

y(x-2) = x

y = x/(x-2)

so the answer is x/(x-2)

You can check out my fiverr account for more help; providing detailed explanations to math questions for only $1per question :)

fiverr name: kesja_